Sidgwick and Rawls on distributive justice and desert - Miller, D (SAGE Publications, 2021)
This article explores, comparatively and critically, Sidgwick’s and Rawls’s reasons for rejecting desert as a principle of distributive justice. Their ethical methods, though not identical, each require giving weight to common sense convictions about justice as well as higher-level principles. Both men, therefore, need to find a substitute for desert that captures some of its content – in Sidgwick’s case ‘quasi-desert’ takes the form of an incentive principle, and in Rawls’s case a principle of legitimate entitlement. However their reasons for rejecting desert are unclear, and at points appear to rest on contestable conceptual or metaphysical claims that their methodological commitments are meant to rule out. To clarify matters, the article distinguishes between three levels at which antidesert arguments may operate: 1) Those purporting to reveal some fundamental defect in the idea of desert itself; 2) Those purporting to show that we cannot find a coherent basis for desert, at least for purposes of social justice; 3) Those purporting to show that it is impossible for social institutions to reward people according to their deserts, no matter which basis is chosen. At each level, the arguments put forward by Sidgwick and by Rawls are shown to be unsound.